1994
DOI: 10.1021/jm00028a017
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and biological evaluation of 5-[[3,5-bis(1,1-dimethylethyl)-4-hydroxyphenyl]methylene]oxazoles, -thiazoles, and -imidazoles: novel dual 5-lipoxygenase and cyclooxygenase inhibitors with antiinflammatory activity

Abstract: A variety of benzylideneoxazoles, -thiazoles, and -imidazoles derived from 2,6-di-tert-butylphenol were prepared and evaluated as dual inhibitors of 5-lipoxygenase and cyclooxygenase in rat basophilic leukemia (RBL-1) cells. The target compounds exhibit varying degrees of selectivity toward the two enzymes. Several compounds are orally active in the rat carageenan footpad edema (CFE) and mycobacterium footpad edema (MFE) antiinflammatory models. Structure-activity relationships are discussed. From this work, (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
71
0

Year Published

1994
1994
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 159 publications
(73 citation statements)
references
References 3 publications
2
71
0
Order By: Relevance
“…Many multisubstituted benzylidenethiazole analogs derived from 2,6-di-tert-butylphenol have been found to reduce inflammatory processes in vivo and in vitro by inhibiting both COX and 5-LOX (Unangst et al, 1994). Previously, we reported that one such analog, 5-(3,5-di-tert-butyl-4-hydroxybenzylidene) thiazolidin-2,4-dione (BHB-TZD), also possesses strong anti-atherogenic activity (Choi et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Many multisubstituted benzylidenethiazole analogs derived from 2,6-di-tert-butylphenol have been found to reduce inflammatory processes in vivo and in vitro by inhibiting both COX and 5-LOX (Unangst et al, 1994). Previously, we reported that one such analog, 5-(3,5-di-tert-butyl-4-hydroxybenzylidene) thiazolidin-2,4-dione (BHB-TZD), also possesses strong anti-atherogenic activity (Choi et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Different reported methodologies on 2-imino-thiazolidin-4-one synthesis imply the isolation and purification of the corresponding thioureas as intermediates, and their subsequent chloroacetylation. [18][19][20] In this work, the quinoline derivatives bearing the 2-imino-tiazolidin-4-one framework 13 and 14 were obtained in good yields as white solids from the quinoline diamines 8, potassium thiocyanate, and chloroacetyl chloride in anhydrous acetone at room temperature, without isolation of thiourea derivatives 13a and 14a (Scheme 1, route A).…”
Section: Synthesis Of 4-aminoquinoline Derivatives Bearing N-heterocymentioning
confidence: 99%
“…Physicochemical characteristics of the obtained compounds are given in Table 2. (13) General procedure for synthesis of chloroquine and 1H-pyrrol-2,5-dione hybrids (15)(16)(17)(18)(19)(20)(21)(22) 1.0 g (4.24 mmol) of quinoline diamines (8a or 8b) was dissolved in 5.0 mL of anhydrous dichloromethane under vigorous agitation. Then, a solution of anhydride (9-11) (0.7 g, 4.24 mmol) in dichloromethane was added dropwise to the above solution for 30 min at 0 °C, stirring the white precipitate formed for 2 h. Solvent excess was distilled under reduced pressure, and the remaining solid was filtered and washed with diethyl ether.…”
Section: Chemistry General Procedures For Synthesis Of 4-amino-7-chlormentioning
confidence: 99%
See 1 more Smart Citation
“…It is di-tert-butyl phenol with thiazole molecular scaffold and has been identified as a dual inhibitor of cellular PGF 2 -alpha (COX pathway) and LTB 4 (LOX pathway) production [4,6]. Darbufelone is orally active and has been shown to be non-ulcerogenic in animal model of inflammation and arthritis [4,6].…”
Section: Introductionmentioning
confidence: 99%